2004
DOI: 10.1007/s00261-004-0247-7
|View full text |Cite
|
Sign up to set email alerts
|

Colon stenosis caused by old portal vein thrombosis

Abstract: A 58-year-old female with a history of portal vein thrombosis was referred to our hospital with abdominal pain and distention. Colon fiber and enema of the colon showed stenosis at the transverse colon and the ascending colon, with edematous mucosa. Laparotomy revealed no abnormal findings other than chronic ischemia of the colon. To our knowledge, this is the first reported case of colon stenosis caused by portal vein thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Of the four patients for whom arterial and portal phase CT images were available (in addition to tissue samples), three patients (3/4, 75%) showed higher enhancement in portal phase than arterial phase, likely due to fibrosis and submucosal capillary dilatation. The radiographic findings associated with post-ischemic strictures mimicked those of various intestinal diseases such as Crohn's disease, NSAID-induced enteropathy and/or CMUSE ( 4 ). A previous report on strictures associated with Crohn's disease showed that it was relatively uncommon at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the four patients for whom arterial and portal phase CT images were available (in addition to tissue samples), three patients (3/4, 75%) showed higher enhancement in portal phase than arterial phase, likely due to fibrosis and submucosal capillary dilatation. The radiographic findings associated with post-ischemic strictures mimicked those of various intestinal diseases such as Crohn's disease, NSAID-induced enteropathy and/or CMUSE ( 4 ). A previous report on strictures associated with Crohn's disease showed that it was relatively uncommon at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, no study has focused on the radiologic features of post-ischemic strictures. A few cases of postischemic stricture have been identified and clinical findings have mainly been described in case reports ( 4 8 9 10 15 ). The cases in this study highlight several important aspects of post-ischemic stricture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few case reports of colon stricture formation from various other rare etiologies. These include iatrogenic superior mesenteric artery injury, portal vein thrombosis, NSAID-induced, colonic cryptococcosis, and amebiasis [15][16][17][18]. To the best of our knowledge, this is the first reported case of hepatic flexure stricture attributed to recurrent ischemic episodes in the same anatomical area.…”
Section: Discussionmentioning
confidence: 99%